Transition‐Metal‐Free [4+3]‐Cycloaddition of ortho‐Quinone Methides and Isomünchnones: Catalytic and Diastereoselective Assembly of Oxa‐bridged Oxazocine Scaffolds. Issue 49 (12th November 2018) - Lam, Heather; Qureshi, Zafar; Wegmann, Marcus; Lautens, Mark
Abstract: Cycloadditions are powerful processes to synthesize complex polycyclic scaffolds. Herein, we disclose a [4+3]‐cycloaddition between an in situ generated ortho ‐quinone methide and an isomünchnone to yield oxa‐bridged oxazocine cores, generating N2 and H2 O as the sole by‐products. Using only catalytic amounts of camphorsulfonic acid, it is possible to generate both reactive intermediates in one step, eliminating the need for rhodium catalysts generally employed for isomünchnone formation. Spectroscopic data and X‐ray crystallography indicate the formation of the syn diastereomer, with the main side‐product arising from a hydrate participating in a competing [4+2]‐cycloaddition pathway. Abstract : A [4+3]‐cycloaddition between an in‐situ‐generated ortho ‐quinone methide and an isomünchnone to yield oxa‐bridged oxazocine cores, generating N2 and H2 O as the sole by‐products, is described. By using only catalytic amounts of camphorsulfonic acid, it is possible to generate both reactive intermediates in one step, eliminating the need for rhodium catalysts generally employed for isomünchnone formation.